Physicochemical profiles of stingless bee (Apidae: Meliponini) honey from South East Asia (Thailand) - Bajaree Chuttong (2018)
© 2015 Elsevier Ltd. Abstract This study examines the physicochemical properties of stingless bee honey from SE Asia (Thailand). Twenty-eight stingless bee honey samples, from 11 stingless bee species, were examined. Results reveal an average color (67 ± 19 mm Pfund), moisture (31 ± 5.4 g/100 g), ash (0.531 ± 0.632 g/100 g), electrical conductivity (1.1 ± 0.780 ms/cm), pH of (3.6 ± 0.198), total acidity (164 ± 162 meq/kg), diastase activity (1.5 ± 1.6°Gothe) and hydroxymethylfurfural (8.7 ± 12 mg/kg). The carbohydrate profile is: total sugar (51 ± 21 g/100 g), fructose (17 ± 9.7 g/100 g), glucose (14 ± 8.6 g/100 g), maltose (41 ± 15 g/100 g) and sucrose (1.2 ± 2.7 g/100 g). These findings are not dissimilar to those reported for stingless bee honeys from the neo-tropics. When compared with the Apis mellifera standard, stingless bee honey is characterized as possessing higher moisture content, acidity, ash and HMF but a lower level of total sugars.